PENERAPAN MODEL PENGAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 006 BENCAH KELUBI KECAMATAN TAPUNG - Darmatias Darmatias; Hendri Marhadi; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problems of this research is the low of students achievement. From the as 27 students was reached the score of KKM 75 as 12 students or 44.44%. awhile the other as 15 students or 55.56% have not yet reached the score of KKM. This research was aimed to improve students achievement of math grade IV SDN 006 Bencah Kelubi District of Tapung with the application of direct teaching model. This research was a classroom action research (PTK). The research subject was the fourth grade students of SDN 006 Bencah Kelubi District of Tapung numbering as many as 27 students consisting of 13 male, 14 female. Data was collected by observation techniques and engineering achievement test. The result of research, know the teacher activities of first meeting as 75.0% with good category. Second meeting as 80.0% with good category, fourth meeting as 85.0% with very good category, and the last meeting as 90.0% with very good category. The students activities first meeting as 65.0% with enough category. Second meeting as 70.0% with good category, fourth meeting as 75.0% with good category, and the last meeting as 80.0% with very good category. The improvements of students achievement from the students base score as 68.0 which complete 55.56% increasing as 89.6 with the complete 88.89 at test I increasing to test II as 94.4 with completeness 100.0%. Based on these results was concluded that by applying the direct teaching model can improve math of students achievement of grade IV SDN 006 Bencah Kelubi District of Tapung.Key Words: Direct Teaching Model, Students Achievement